Understanding the activity and stability of Lewis acid-modified Ziegler–Natta catalysts for the sustainable production of polypropylene - Rafik Rajjak Shaikh; Yodsamol Sainu; Supareak Praserthdam; Piyasan Praserthdam (Journal of Taibah University for Science, 2025)
Cleaner polymer production involves minimizing environmental impact by using efficient catalysts and eco-friendly synthesis methods. Identifying active and stable catalysts is essential. This study explored the effect of Lewis acids (FeCl2, MnCl2, SiCl4 and ZnCl2) on the reducibility of titanium-based MgCl2 and Mg(OEt)2 supported precatalysts in propylene polymerization when combined with a cocatalyst, trimethylaluminum. Lewis acid modification of precatalysts containing internal donors, ethanol and tetrahydrofuran, increased catalyst surface area without drastically altering overall composition. Furthermore, surface titanium levels influenced the response to trimethylaluminum, with higher titanium promoting a faster cocatalyst response. This trend, however, was not evident in tetrahydrofuran-based catalysts. Importantly, product yields were consistently higher with Lewis acid-modified catalysts. The interaction between Lewis acids and titanium plays a pivotal role. This study advances the understanding of Ziegler–Natta catalysts for cleaner polymer production.